AVALIAÇÃO DO PROCESSO DE IMPLEMENTAÇÃO DE OBRAS PÚBLICAS EM UNIVERSIDADES FEDERAIS: UM ESTUDO DO PROGRAMA REUNI - Maria Fernanda Nogueira Bittencourt (Universidade Federal de Santa Catarina, 2017)
This work was carried out to evaluate infrastructure projects of the REUNI Program, in order to identify the main factors contributing to its completion, delay or suspension in federal higher education institutions, as well as its consequences for the achievement of the goals of this Program. Currently there is a lack of studies correlating public works to the policy cycle. Despite the fact that increase in public service provision normally leads to an expansion of the installed structure, literature studies seldom refer to this subject. The method used in the work is the case study, where the studied object is REUNI, understood as a government program for restructuring and expansion of higher education federal. For this work, data collection and analyses of infrastructure work of the fifty-three federal universities participants REUNI collected from a bibliographic and documentary research. Among its findings, works completed has reached 78%; engineering and architecture teams were renovated and enlarged; agreed vacancies and courses within the universities were surpassed in total numbers; while of contracted resource investment was available and also expanded in 62.55%. Despite this, results show that little attention was paid to work in formulation of REUNI, as many works have suffered outages, project revisions and additives. Finally, it is noteworthy that for three-quarters of universities the non-completion of any work brought negative impacts on implementation of new vacancies or new programs, thereby demonstrating the importance of work on the achievement of the agreed goals of a public policy.